Exploring the Impact of Parental Nutrition Literacy on Early Childhood Physical-Motor Development: A Case Study - Cucu Ailah; Nita Priyanti; Rita Intan Anggraeni (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
This study examines the impact of parental nutrition literacy on the physical-motor development of children at TK Al-Falah. Using a case study approach, data were collected through questionnaires and observations, and analyzed thematically. The findings suggest that parents with a strong understanding of nutrition are more likely to provide balanced, nutritious meals, which positively influence their children's physical-motor development. Children of parents with high nutrition literacy exhibit greater physical activity, improved balance, and enhanced fine and gross motor coordination. In contrast, children of parents with limited nutrition knowledge tend to have less balanced diets, potentially hindering their physical development. These results underscore the importance of nutrition education for parents to ensure children receive adequate nourishment for optimal physical-motor growth. It is recommended that schools and relevant organizations strengthen nutrition education initiatives to support children's overall development.